Susceptible-Infected-Recovered (SIR) model to measure the virality of breaking news on Facebook / Noorzila Sharif ... [et al.] - Sharif, Noorzila; Bidin, Jasmani; Ku Akil, Ku Azlina; Rizan, Nur Natasha Arisha (UiTM Cawangan Perlis, 2021)
Susceptible-Infected-Recovered (SIR) model has been used worldwide to measure the spreading of covid-19 in the community. Apparently, the spreading nature of the covid-19 virus and any other contagious disease is quite similar with the spreading of breaking news through social media. This study was carried out to analyze the dynamics spread of one selected news content on Facebook using SIR models with demography and without demography. From the news, the numbers of likes, comments, shares, views as well as the number of followers of the Facebook account have been collected to calculate reproduction number. For SIR without demography, the reproduction number (Ro) is 1.69, indicates that for every 100 Facebook users who received the news, they will probably share the news to other 169 Facebook users. The value of R0 is slightly lower (1.58) for SIR with demography. This preliminary study could be extended by considering a lot more observations and by testing different parameters value due to any further action imposed after the news spreading out.